Kemampuan Pemecahan Masalah Matematis: Sebuah Kajian Literatur - Akbar Ramadhan; Tomo; Ahmad Yani T; Nadya Febriani Meldi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Mathematics is formed from human experience in the world empirically. Then the experience is processed in the world of ratios, processed analytically with reasoning in the cognitive structure so that mathematical concepts are formed so that the mathematical concepts formed are easily understood by other people and can be manipulated appropriately, then mathematical language or mathematical notation is used. global value. In this research, the author examines the understanding of problem solving based on several experts and research that has been carried out and draws conclusions from the literature review. The type of research used in this study is Library Research by searching for various articles from national and international journals on Google Scholar which are useful as a theoretical basis for the topic discussed, namely mathematical problem solving abilities. Mathematical problem solving ability is thinking that is directed directly to finding a solution or solution to a specific problem in the development of high-level thinking that can connect several concepts.